SEXUAL INTIMIDATION AND DESIRE FOR GOOD GRADES: UNDERSTANDING THE DYNAMICS OF ‘SEXUALISED GRADES’ IN NIGERIAN UNIVERSITIES - Saheed, Rahman Olanrewaju; Saliman, Salahu Tunde; Edicha, Abdulmalik (African Journal of Social and Behavioural Sciences, 2024)
Sexual intimidation, a form of sexual and gender-based violence within academic institutions remains a global concern, raising socio-legal and psychological implications. The heightened sensitivity of such acts within institutions dedicated to knowledge dissemination underscores the urgency of understanding the multifaceted factors at play. Hence, this study delves into the prevalent issue of ’sexualised grades’ at the Federal University Wukari, Nigeria, exploring how the power imbalance between lecturer and students on one hand, and the desire for good grades by the students contributes to the phenomenon of sexualised grades. The study engaged a sample of 255 undergraduate students, employing quantitative research methods. Chi-square tests were employed to analyse the statistical significance of key findings. The research establishes a compelling connection between students and lecturers, revealing a pattern where sexual favours are exchanged for academic success. The study revealed a significant relationship between male lecturers demanding sex from the students and the prevalence of sex for grades (χ²=22.92, P<0.001); the study further revealed that lack of sexual discipline among lecturers is a contributing factor to the prevalence of sex for grade (χ²=29.75, P<0.001). Additionally, the study unveils the significant relationship between peer influence and the practice of sex for grade (χ²=53.60, P<0.001). Lastly, the study revealed a significant relationship between academic laziness of female students and the practice of sex for grade (χ²=88.81, P<0.001). Thus, the issue of sex for grade transcends a simple power imbalance and extends into the realm of individual agency and personal choices. Hence, the study recommends redesigning communication channels for enlightenment campaigns, comprehensive workshops, and seminars for both staff and students to address socio-psychological temptations. Institutional policies should undergo review to ensure strict compliance and foster a culture that prioritizes ethical conduct. In conclusion, the study emphasizes that the prevalence of ’sex for grade’ within academic institutions is a problematic and multifaceted issue that reveals a complex interplay of power dynamics and individual motivations.